Managing monetary policy normalization - Gianluca Benigno; Pierpaolo Benigno (Federal Reserve Bank of New York, 2022)
We propose a new framework for monetary policy analysis to study monetary policy normalization when exiting a liquidity trap. The optimal combination of reserves and interest rate policy requires an increase in liquidity (reserves) a few quarters after the policy rate is set at the effective lower bound. Removal of accommodation requires that quantitative tightening starts before the liftoff of the policy rate. Moreover, the withdrawal of liquidity takes place at a very slow pace relative to the normalization of the policy rate.
Keywords: E31; E43; E52; E58; 330; reserve management; central bank balance sheet; quantitative tightening; quantitative easing; interest on reserves